Storage stability of berry mueslis with special focus on phenolic compounds - Zhou, Ying; Saarniit, Kärt; Jafari, Mahsa Sadat; Rosenvald, Sirli; Laaksonen, Oskar; Tian, Ye; Yang, Baoru (Elsevier BV, 2025)
To investigate stability of phenolic compounds in food products during storage, real-time (RT, at 23 °C) and accelerated shelf-life tests (ASLT, 40 °C) were conducted on modified-atmosphere-packaged strawberry, blueberry, and blackcurrant mueslis. Monitored with LC-MS and HPLC, a clear variation was observed in the phenolic profile of the berry mueslis in both tests, including 29 anthocyanins, 40 flavonols, 16 phenolic acids, and 2 flavan-3-ols. The contents of these phenolic compounds changed differently during storage. Unlike other phenolics, the contents of all identified anthocyanins were significantly decreased in the tests. The modified atmosphere package of the mueslis did not retard anthocyanin degradation at 40 °C. The largest decrease occurred in the first 56 days of ASLT, when 54–66 % of total anthocyanins were lost. The degradation was highly associated with structural features of anthocyanins, including substitution on both anthocyanidins and sugar moieties. Pelargonidin 3-O-glucoside, malvidin 3-O-arabinoside, and malvidin 3-O-galactoside had higher degradation rates (k = 0.0267, 0.0195, and 0.0176 day−1, respectively) than others. Acylation on the sugar moieties also significantly enhanced storage stability of anthocyanins. Our results suggested that the stability of bioactive phytochemicals in food products should be considered when estimating the health-promoting function and sensorial property of the products.